Disgust Toward Sex-Relevant and Sex-Irrelevant Stimuli in Pre-, Early, and Middle Adolescence. Issue 1 (2nd January 2019) - Borg, Charmaine; Hinzmann, Jessica; Heitmann, Janika; de Jong, Peter J.
Abstract : For prepubertal youth, sexual stimuli elicit disgust and avoidance, yet in adolescence this avoidance shifts to sexual approach. One explanation could be that disgust declines in adolescence. This project examined whether disgust is indeed lower in adolescence compared to preadolescence, and whether this difference across age groups would be restricted to sex-relevant disgust elicitors. We also examined whether the strength of disgust would depend on familiarity between participant and source. To examine disgust responses in youths, two cross-sectional studies ( N = 248, ages six to 17 years) were conducted using scenario-based measurements. Disgust was overall higher in early adolescence than in preadolescence and relatively weak when the source of disgust was a familiar person. Specifically, when parents were the source, sex-relevant disgust was higher in the groups of early and middle adolescents than in the group of preadolescents. Sex-relevant disgust elicited by a stranger or best friend, however, was lower in middle than in early adolescence. The latter is consistent with the view that repeated confrontation with disgusting stimuli might attenuate disgust, which could contribute to healthy sexual functioning. The heightened sex-relevant disgust in middle adolescents when parents were the source might reflect a functional avoidance mechanism of inappropriate sex mates.